Tunable C + L bands triple frequency spacing multi-wavelength Brillouin-erbium fiber laser - Ismail A.; Al-Mansoori M.H.; Abdullah F.; Jamaludin M.Z.; Al-Qartoubi M.; Almamari S.H.; Alkhaldi H.S. (Academic Press Inc., 2023)
Brillouin scattering; Erbium; Fiber lasers; Optical communication; Brillouin pump; Brillouin Stokes; Brillouin-erbium fiber lasers; Combined techniques; Multi-wavelengths; Triple frequency; Virtual mirror; Wide tuning range; Laser mirrors